Solidarity, responsibility and group identity - Jano Costard; Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2011)
In the Solidarity Game (Selten and Ockenfels, 1998) lucky winners of a lottery can transfer part of their income to unlucky losers. Will losers get smaller transfers if they can be assumed to be (partly) responsible for their zero income because they have chosen riskier lotteries (Trhal and Radermacher, 2009)? Or will risk-lovers and risk-averters develop group identity feelings, leading to larger transfers within, rather than between, the groups (Chen and Li, 2009, for charitable transfers between and within otherwise defined groups)? In an experiment we find behavior to be guided by in-group favoritism. Responsibility for self-inflicted neediness does not seem to play an important role. In-group/out-group behavior is successfully described by a variant of a social utility function suggested by Cappelen et al. (2010).
Keywords: D3; D8; 330; risky behavior; group identity; solidarity